Partnership for Evidence-Based Agri-Food Policy Research (Egypt) - Dhehibi, Boubaker; Salem, Shaban Ali; Abd-Allah, Emman; M. Oumer, Ali; Akramov, Kamiljon; Baum, Michael (2023)
On the 11th of June 2023, the International Center for Agricultural Research in the Dry Areas (ICARDA) and the Agricultural Research Center (ARC) of the Ministry of Agriculture and Land Reclamation of Egypt (MoALR) organized a Multistakeholder Workshop titled “To a Better Partnership for Evidence-based Agrifood Policy Research.” The workshop agenda is provided in Appendix 1. About 29 representatives of stakeholders attended the workshop, including high-level policymakers, researchers, and delegates fro various agricultural and food policy organizations. The purpose of this workshop was to promote a national expert network of evidence-based policy research to design and implement a long-run country work plan for the resilient agricultural and agrifood systems in Egypt.